Acute heart failure: is ACTION-ICU useful?. (11th May 2021) - Santos, M; Paula, S; Santos, H; Almeida, I; Miranda, H; Sa, C; Chin, J; Almeida, S; Sousa, C; Tavares, J; Santos, L; Almeida, ML
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Patients (pts) with acute heart failure (AHF) are a heterogeneous population. Risk stratification at admission may help predict in-hospital complications and needs. ACTION ICU score is validated to estimate the risk of complications requiring ICU care in non-ST elevation acute coronary syndromes. Objective: To validate ACTION-ICU score in AHF as predictor of in-hospital M (IHM), post discharge early M [1-month mortality (1mM)] and 1-month readmission (1mRA), in our center population, using real-life data. Methods: Based on a single-center retrospective study, data collected from pts admitted in the Cardiology department with AHF between 2010 and 2017. Pts without data on previous cardiovascular history or uncompleted clinical data were excluded. Statistical analysis used non-parametric tests, logistic regression analysis and ROC curve analysis. Results: We included 300 pts admitted with AHF. Mean age was 67.4 ± 12.6 years old and 72.7% were male. 37.7% had previous history of revascularization procedures, 66.9% had hypertension, 41% were diabetic and 38% had dyslipidaemia. Mean heart rate was 95.5 ± 27.5bpm, mean systolic blood pressure (SBP) was 131.2 ± 37.0mmHg, mean urea level at admission was 68.8 ± 40.7mg/dL, mean sodium was 137.6 ± 4.7mmol/L, mean glomerular filtration rate (GFR) was 57.1 ± 23.5ml/min. 35.3% were admitted in Killip-Kimball class (KKC) 4. Mean ACTION-ICU score was 10.4 ± 2.3. Inotropes' usage was necessary in 32.7% of the pts, 11.3% of the pts needed non-invasive ventilation (NIV), 8% needed invasive ventilation (IV). IHM rate was 5% and 1mM was 8%. 6.3% of the pts were readmitted 1 month after discharge. Older age (p < 0.001), lower SBP (p = 0, 035), presenting in KKC 4 (p < 0.001, OR 8.13) and need of inotropes (p < 0.001) were predictors of IHM in our population. Older age (OR 1.06, p = 0.002, CI 1.02-1.10), lower SBP (OR 1.01, p = 0.05, CI 1.00-1.02) and lower left ventricle ejection fraction (LVEF) (OR 1.06, p < 0.001, CI 1.03-1.09) were predictors of need of NIV. None of the studied variables were predictive of need of IV. LVEF (OR 0.924, p < 0.001, CI 0.899-0.949), lower SBP (OR 0.80, p < 0.001, CI 0.971-0.988), higher urea (OR 1.01, p < 0.001, CI 1.005-1.018) and lower sodium (OR 0.92, p = 0.002, CI 0.873-0.971) were predictors inotropes' usage. ACTION-ICU was able to predict IHM (OR 1.51, p = 0.02, CI 1.158-1.977), 1mM (OR 1.45, p = 0.002, CI 1.15-1.81) and inotropes' usage (OR 1.22, p = 0.002, CI 1.08-1.39), but not 1mRA, the need of IV or NIV. ROC curve analysis revealed ACTION-ICU performs well when predicting IHM (Area under curve (AUC) 0.729, confidence interval (CI) 0.59-0.87), inotropes' usage (AUC 0.619, CI 0.54-0.70) and 1mM (AUC 0.705, CI 0.58-0.84). Conclusion: In our population, ACTION-ICU score was able to predict IHM, 1mM and inotropes's usage.